Penyelesaian Sengketa antara Konsumen dengan Pelaku Usaha yang Berbasis Pada Wanprestasi Atas Perjanjian Pembiayaan: (Studi Kasus: Putusan Mahkamah Agung Nomor 481K/Pdt.Sus-BPSK/2015) - Muh. Afdal Yanuar (Dialogia Iuridica, 2022)
The purpose of this paper is to describe the object and mechanism for disputes resolution mechanism between consumers and business actors based on Law Number 8 of 1999 concerning Consumer Protection, and disputes resolution between consumers and business actors based on default on financing agreements. (Case Study of Supreme Court Decision Number 481K/Pdt.Sus-BPSK/2015). The background issue in this paper is because there is still a Consumer Dispute Settlement Agency (BPSK) which considers that disputes between consumers and business actors based on financing agreements are ‘consumer disputes’, when it should be a ‘default dispute’ that is tried in the District Court. This paper uses normative research with a statute, conceptual, and case approach. The results of this paper illustrate that the object of dispute between business actors and consumers as determined under the Consumer Protection Law is 'consumer disputes', that is disputes arising from consumers suffering damage, and/or consumer losses due to consuming goods and/or services produced by business actors. Furthermore, the mechanism for resolving consumer disputes can be done by, consumers file a consumer dispute lawsuit which is resolved in the form of non-litigation (through BPSK) or litigation (through the district court). Moreover, in the context of a dispute between a consumer and a business actors based on a default on a financing agreement, the lawsuit submitted is a 'defaults' lawsuit, which is directly submitted to the District Court. This has also become a legal consideration in the Supreme Court's Decision Number 481K/Pdt.Sus-BPSK/2015, and several jurisprudence related to the case.